2003
DOI: 10.1091/mbc.e03-03-0150
|View full text |Cite
|
Sign up to set email alerts
|

Pex11-related Proteins in Peroxisome Dynamics: A Role for the Novel Peroxin Pex27p in Controlling Peroxisome Size and Number inSaccharomyces cerevisiae

Abstract: Transcriptome profiling identified the gene PEX25 encoding Pex25p, a peroxisomal membrane peroxin required for the regulation of peroxisome size and maintenance in Saccharomyces cerevisiae. Pex25p is related to a protein of unknown function encoded by the open reading frame, YOR193w, of the S. cerevisiae genome. Yor193p is a peripheral peroxisomal membrane protein that exhibits high sequence similarity not only to Pex25p but also to the peroxisomal membrane peroxin Pex11p. Unlike Pex25p and Pex11p, Yor193p is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 53 publications
7
103
0
Order By: Relevance
“…PEX27 remain constant, in S. cerevisiae during incubation in oleic acid medium (Erdmann and Blobel, 1995;Smith et al, 2002;Tam et al, 2003). Semi-quantitative RT-PCR was performed to determine transcript levels of the PEX11, PEX11C and PEX11/25 genes in Y. lipolytica during a switch from glucose medium to oleic acid medium (Fig.…”
Section: Y Lipolytica Pex11 Protein Family Members Are Peroxisomal Imentioning
confidence: 99%
See 2 more Smart Citations
“…PEX27 remain constant, in S. cerevisiae during incubation in oleic acid medium (Erdmann and Blobel, 1995;Smith et al, 2002;Tam et al, 2003). Semi-quantitative RT-PCR was performed to determine transcript levels of the PEX11, PEX11C and PEX11/25 genes in Y. lipolytica during a switch from glucose medium to oleic acid medium (Fig.…”
Section: Y Lipolytica Pex11 Protein Family Members Are Peroxisomal Imentioning
confidence: 99%
“…Confocal fluorescence microscopy (Tower et al, 2011), electron microscopy and morphometric analysis (Eitzen et al, 1997;Tam et al, 2003), and immunofluorescence microscopy (Tam and Rachubinski, 2002) were performed as described previously.…”
Section: Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Since only Pex11␣p is stimulated by hypolipidemic drugs, this isoform was supposed to be involved in the induced proliferation, whereas Pex11␤p might regulate the constitutive process (66). Similarly, in S. cerevisiae, a family of Pex11p proteins comprising Pex11p, Pex25p, and Pex27p was identified that is required for peroxisome biogenesis regulating peroxisome abundance (67,68). Recently, an interaction between Pex25p and the small GTPase Rho1p was suggested to play a role in controlling yeast peroxisome membrane dynamics (69).…”
Section: Arfs Regulate Peroxisome Proliferation In Yeast-mentioning
confidence: 99%
“…Using many different organisms as experimental models (from Saccharomyces cerevisiae to mammalian cells), several laboratories have been quite successful in the task of identifying the genes involved in peroxisomal biogenesis. Almost 30 different genes involved in this process are known (3,5,9,16,17). The proteins they encode are designated by the word peroxin (Pex) followed by a number reflecting the order of their discovery (18).…”
mentioning
confidence: 99%